Practicing for the Future: Deliberate Practice in Early Childhood. Issue 6 (23rd October 2017) - Brinums, Melissa; Imuta, Kana; Suddendorf, Thomas
Abstract : Deliberate practice is essential for acquiring a wide range of skills that have been central to humans' adaptive success, yet little is known about when and how children develop this capability. The current study examined 4‐ to 7‐year‐olds' ( N = 120) ability to selectively practice a skill that would be useful in the near future, as well as their broader understanding of the role of deliberate practice in skill acquisition. Six‐ and 7‐year‐olds demonstrated both an explicit understanding of deliberate practice and the capacity to practice without being prompted. Five‐year‐olds showed an understanding of deliberate practice and some capacity to practice, whereas 4‐year‐olds showed neither of these capabilities. Findings reveal important developments in children's future‐directed behavior beyond the preschool years.